Does Prior Stroke Predict Long-Term Recurrent Stroke After Percutaneous Coronary Intervention? Five-Year Results From a Large Cohort Study - Xu, Jing-jing; Jia, Si-da; Zhu, Pei; Jiang, Lin; Jiang, Ping; Song, Ying; Zhao, Xue-yan; Li, Jian-xin; Chen, Jue; Yang, Yue-jin; Gao, Run-lin; Qiao, Shu-bin; et al. (Frontiers in Neurology, 2021)
Background: We found a positive correlation between the prior stroke history and recurrent stroke in patients who underwent percutaneous coronary intervention (PCI) in our previous study, which indicated the close interaction of stroke and cardiovascular diseases. However, it is unclear whether prior stroke is still associated with worse prognosis at a longer follow-up period. Methods: A total of 10,724 coronary heart disease (CHD) patients who received PCI from January to December 2013 were prospectively enrolled and were subsequently divided into the prior stroke (n = 1,150) and non-prior stroke (n = 9,574) groups according to their history. Baseline characteristics and 5-year outcomes were recorded. Results: Patients with prior stroke had more clinical risk factors, as well as more extensive coronary artery lesions. Although in-hospital outcomes were similar between patients from the two groups, the 5-year follow-up result revealed that patients with prior stroke experienced higher incidence of stroke, major adverse cardiac and cerebrovascular events (MACCEs), all-cause death, and cardiac death (7.0 vs. 3.0%, p < 0.001; 25.9 vs. 20.3%, p < 0.001; 5.3 vs. 3.5%, p = 0.002; 3.1 vs. 2.1%, p = 0.032, respectively). After the propensity score matching, the 5-year stroke rate was still higher in the prior stroke group (6.8 vs. 3.4%, p = 0.001). The multivariable regression analysis also identified the prior stroke as a risk predictor of the 5-year stroke (HR = 2.011, 95% CI: 1.322–3.059, p = 0.001). Conclusions: Coronary heart disease patients with prior stroke who received PCI had a higher incidence of 5-year long-term adverse cardiovascular and cerebrovascular events, especially recurrent stroke. Prior stroke was a strong risk predictor of future stroke events.